Dampak Penerapan Persyaratan Surat Tes Kesehatan Pranikah terhadap Praktik Nikah Siri - Julianti, Alvionita; Lubis, Azwani (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to understand the impact of implementing premarital health test certificate requirements on unregistered marriage practices in Ujung Batu III Village. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that implementing premarital health test certificate requirements in Ujung Batu III Village has a complex impact on unregistered marriage practices. Although this policy aims to raise awareness about the importance of reproductive health and prevent early marriage, it has become an obstacle for some prospective couples who choose unregistered marriage. This is due to several factors, such as a lack of understanding about the importance of health tests, concerns about privacy and social stigma, conflicts between state law and religious law, and the prevalence of early marriage. Therefore, it is recommended that the Religious Affairs Office of Hutaraja Tinggi Sub-district intensify outreach and education about the importance of premarital health tests and their implications, especially for couples potentially engaging in unregistered marriage. The Ujung Batu III Village Government needs to strengthen coordination with the Religious Affairs Office and health institutions and involve community and religious leaders in disseminating the policy and providing guidance to prospective couples. Health institutions must improve the accessibility and quality of premarital health test services, including expanding the scope of examinations and providing comprehensive counseling. Community and religious leaders should play an active role in educating the public about the importance of healthy and registered marriages and help eliminate the stigma associated with health tests and early marriage. The community needs to proactively seek information about reproductive health, understand the importance of premarital health tests, and support government efforts in preventing early marriage and unregistered marriages.